2015
DOI: 10.1007/s11906-015-0547-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pulmonary Hypertension and Right Heart Failure in the Intensive Care Unit

Abstract: Management of acute right ventricular failure, both with and without coexisting pulmonary hypertension, is a common challenge encountered in the intensive care setting. Both right ventricular dysfunction and pulmonary hypertension portend a poor prognosis, regardless of the underlying cause and are associated with significant morbidity and mortality. The right ventricle is embryologically distinct from the left ventricle and has unique morphologic and functional properties. Management of right ventricular fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Appropriate sinus heart rate and rhythm, and the maintenance of atrioventricular synchrony and atrial kick, can be among the simplest methods of maintaining and avoiding RV contractility impairment. Electrical or pharmacological cardioversion for the restoration of sinus rhythm and the placement of a temporary pacemaker if heart block is present should be considered [ 80 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate sinus heart rate and rhythm, and the maintenance of atrioventricular synchrony and atrial kick, can be among the simplest methods of maintaining and avoiding RV contractility impairment. Electrical or pharmacological cardioversion for the restoration of sinus rhythm and the placement of a temporary pacemaker if heart block is present should be considered [ 80 ].…”
Section: Treatmentmentioning
confidence: 99%
“…We have described general management considerations for critically ill patients with acute RVF. A key principle in the management of acute RVD focuses on determination and treatment of the underlying etiology [ 80 ]. We briefly review targeted therapy for some specific causes of acute RVF ( Table 5 ).…”
Section: Treatmentmentioning
confidence: 99%
“…138,139 The common precipitants include: (1) anemia; (2) arrhythmias (i.e., supraventricular tachycardias); (3) hypoxemia; (4) hypotension; (5) hypo-/ hyperthyroidism; (6) infection; (7) myocardial infarction; (8) pregnancy; (9) pulmonary embolism; and (10) withdrawal of PH therapy. 140 In one prospective single-center study of 46 patients, infection was found to be most common and associated with poor prognosis. 141 Hence, early identification of infection and prompt administration of empiric antimicrobial therapy are essential in the ICU.…”
Section: Decompensated Right Ventricular Failurementioning
confidence: 99%
“…In addition, the RV is easily distensible and can accommodate various changes in venous return due to posture, volume status, and respiration while maintaining adequate cardiac output [27]. The interaction of the forces transmitted from one ventricle to the other through the myocardium and pericardium is referred to as ventricular interdependence, and it is vital for ventricular synchrony [29,41]. The pressure difference between the two ventricles is referred to as the transseptal gradient and is typically around 100 mmHg [82].…”
Section: Pathophysiologymentioning
confidence: 99%